Fenomena Kelimpahan Sumber Daya Alam dan Natural Resource Curse Dalam Perspektif Ekonomi Di Pulau Sumatera - Finka Amalia; Zulfa Emalia (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Abundance of natural resources is a boon for the region that has them. However, there is a paradox that states that the abundance of natural resources can have a negative effect on economic growth, this phenomenon is called the Natural Resource Curse. Several studies have found that the abundance of natural resources can have a negative effect on economic growth. This study will examine whether the Natural Resource Curse phenomenon at the provincial level on Sumatra Island in the 2014-2019 period and examine the value of the Natural Resource Curse by using an index called the Regional Resource Curse Index (RRCI) with two indicators namely, the Natural Resource Curse Index (NRDI) and the Regional Sustainable Development Index (RSDI). The research uses panel data regression analysis, conducted by looking at the effect of the abundance of natural resources on economic growth. The results showed that the abundance of natural resources that used mining and oil and gas revenue-sharing had a positive and insignificant effect on economic growth. This proves that the Natural Resource Curse phenomenon does not occur at the provincial level on the island of Sumatra in the 2014-2019 period. However, based on the RRCI value, it shows that provinces with richer natural mining resources tend to face a higher Natural Resource Curse phenomenon. As a result, Jambi Province is the region with the highest RRCI of 1.26, with an NRDI of 54.9 and an RSDI of 53.9.